Soft X-ray excess in the Coma cluster from a cosmic axion background - Angus, Stephen; Conlon, Joseph P.; Marsh, M. C. David; Powell, Andrew J.; Witkowski, Lukas T. (Journal of cosmology and astroparticle physics, 2014)
We show that the soft X-ray excess in the Coma cluster can be explained by a cosmic background of relativistic axion-like particles (ALPs) converting into photons in the cluster magnetic field. We provide a detailed self-contained review of the cluster soft X-ray excess, the proposed astrophysical explanations and the problems they face, and explain how a 0.1- 1 keV axion background naturally arises at reheating in many string theory models of the early universe. We study the morphology of the soft excess by numerically propagating axions through stochastic, multi-scale magnetic field models that are consistent with observations of Faraday rotation measures from Coma. By comparing to ROSAT observations of the 0.2- 0.4 keV soft excess, we find that the overall excess luminosity is easily reproduced for gaγγ ∼ 2 × 10-13 Ge -1. The resulting morphology is highly sensitive to the magnetic field power spectrum. For Gaussian magnetic field models, the observed soft excess morphology prefers magnetic field spectra with most power in coherence lengths on 𝒪(3 kpc) scales over those with most power on 𝒪(12 kpc) scales. Within this scenario, we bound the mean energy of the axion background to 50 eV≲ ⟨ Ea ⟩ ≲ 250 eV, the axion mass to ma ≲ 10-12 eV, and derive a lower bound on the axion-photon coupling gaγγ ≳ √(0.5/Δ Neff) 1.4 × 10-13 Ge -1.
Gesehen am 04.09.2020